OPERATIONAL AUDIT TO ASSES EFFECTIVENESS OF MEDICAL INVETORY MANAGEMENT AT DEDY JAYA HOSPITAL BREBES - Anugrah, Muhammad Fahmi (Jurnal Ilmiah Mahasiswa FEB, 2016)
This research is about operational audit of medical inventory management at Dedy Jaya Hospital Brebes aimed to assess the effectiveness of the   medical inventory management, indentified weaknesses, gave recommendation and improve medical inventory management in pharmacy installation Dedy Jaya hospital Brebes. The research method used qualitative descriptive research methods. The research data is conducted by field studies through interview, observations and documentations. The analysis of data that used in the research was the qualitative analysis methods. The scope of research is focused on inventory management only as a medicine that includes 24 hour pharmacy service, planning, procurement and reception supplies pharmateuical, medicine storage, management of medicine expiration, the officer who reviewed medicine orders, waiting time, pharmaceutical supplies provisioning request from room service to the warehouse, distribution from warehouse to service unit and other units. Based on the results of the research note that medical inventory management at Dedy Jaya Hospital Brebes has been running effectively because all aspect of management of medical supllies have been conducted in accordance with existing regulations but there are still some flaws that can weaken the operational activities  of  the  company  itself.  Medical  inventory  management  at  Dedy  Jaya Hospital Brebes is already running in accordance with existing policy. Based on the results of the audit finding over weakness of medical inventory management at Dedy Jaya  Hotel,  researchers  provide  recommendations  and  improvements  that  can  be made as consideration so that the company can be more effective in carrying out its operational activities in particular for medical inventory management.   Keywords : Operational Audit, Effectiveness, Inventory, and Management